Science World [motion pictures] Space science : the Solar System; - the sun and its energy; - beyond the solar system. (Coronet/MTI Film and Video, 1989)
Science World ... journeys from depths of the ocean to the outer reaches of the galaxy. Spectacular photography in award-winning programs expolres the basic framework of our world.